2020
DOI: 10.1001/jamanetworkopen.2020.2583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Telehealth Early Palliative Care Intervention for Family Caregivers of Persons With Advanced Heart Failure

Abstract: IMPORTANCE Family caregivers of persons with advanced heart failure perform numerous daily tasks to assist their relatives and are at high risk for distress and poor quality of life. OBJECTIVE To determine the effect of a nurse-led palliative care telehealth intervention (Educate, Nurture, Advise, Before Life Ends Comprehensive Heart Failure for Patients and Caregivers [ENABLE CHF-PC]) on quality of life and mood of family caregivers of persons with New York Heart Association Class III/IV heart failure over 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…Previous studies have demonstrated the beneficial effects of palliative care in patients with conditions such as advanced cancer 28 - 31 and advanced heart failure. 32 , 33 A recent randomized controlled trial of early palliative care involvement in critically ill ICU patients resulted in increased use of hospice services, and a decrease in burdensome interventions at the end-of-life such as tracheostomies, without an increase in mortality compared to patients receiving usual care. 34 The patients and families in our cohort received frequent psychosocial support and counseling from the interdisciplinary palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effects of palliative care in patients with conditions such as advanced cancer 28 - 31 and advanced heart failure. 32 , 33 A recent randomized controlled trial of early palliative care involvement in critically ill ICU patients resulted in increased use of hospice services, and a decrease in burdensome interventions at the end-of-life such as tracheostomies, without an increase in mortality compared to patients receiving usual care. 34 The patients and families in our cohort received frequent psychosocial support and counseling from the interdisciplinary palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…(Powell et al, 2017). ENABLE has demonstrated success in multiple oncology clinical trials (Bakitas et al, 2009;Bakitas, Tosteson, et al, 2015) and was most recently tested in patients with advanced HF, where it showed a potential benefit to patients experiencing poor QOL and their family caregivers Dionne-Odom et al, 2020). ENABLE is initiated at diagnosis of advanced disease and consists of two primary components: (1) an in-person outpatient comprehensive PC assessment by a board-certified provider and (2) a series of six weekly, 30-60 min telephone nurse-led coaching sessions using the Charting Your Course© guidebook (see Figure 1).…”
Section: Telehealth Examples From Research and Clinical Practicementioning
confidence: 99%
“…family, and the healthcare team, a common misperception is that PC cannot provide the same degree of human compassion using remote technology (Andone & Artemis, 2019). Despite this concern, a number of telephone-based PC studies have been conducted, yielding positive results for both patients and caregivers (Bakitas et al, 2004(Bakitas et al, , 2009Bakitas, Tosteson, et al, 2015;Dionne-Odom et al, 2020). Although there is ample evidence that telehealth enhances patient access to PC services, some still considered providing PC via telehealth as "nontraditional" (Guzman et al, 2020).…”
mentioning
confidence: 99%
“… 253 Dionne-Odom and colleagues (2020) suggest early telehealth-base interventions targeting distressed caregivers and assessing caregiver effects on patient outcomes. 256 They proposed an early longitudinal 6-week phone intervention that includes all aspects of palliative care and self-care. 256 While implementation of telehealth-based interventions for underserved and rural non-Hispanic Black communities are strongly encouraged, the acceptability, feasibility, and effectiveness of these programs need to be carefully tested.…”
Section: Completion Of Advance Care Planning and Directivesmentioning
confidence: 99%